Perspectives on Research Recent Findings and Future Directions: A Report of the Iowa Research Consortium for Learning Disabilities - Iowa State Dept. of Education, Des Moines. Bureau of Special Education; Hollinger, Timothy; Iowa State Dept. of Education, Des Moines. Bureau of Special Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
The monograph addresses the issue of research on learning disabilities (LD) and proposes directions for research in Iowa by means of four articles, a report of a survey of needed research, and six brief response papers. The first paper, "Issues on the Identification of Learning Disabled Children" (S.W. Ehly), discusses the problems of identification and assessment and encourages data gathering by classroom teachers. The second paper, "Efficacy of Treatment in Learning Disabilities" (R. D. Tucker), provides a review of the research literature concerned with (1) placement vs. nonplacement, (2) integrated models, and (3) efficacy of specific treatments. "Effective Methods of Instruction for the Learning Disabled" (R. Owens), looks at such issues as use of assessment data to study LD subtypes and intervention effectiveness. The final paper, "Report of the Institutes for Research in Learning Disabilities" (D. Baum) notes the emphasis by the five institutes on the teaching of cognitive strategies to enhance learning and recall and the need for field testing of developed materials and strategies. The survey of research needs (J.H. Reese) reports the areas of program effectiveness and instructional effectiveness identified most frequently. Response papers support, clarify, extend, and/or provide a different perspective on the four leading articles. (DB)
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Processes; Elementary Secondary Education; Handicap Identification; Instructional Effectiveness; Instructional Materials; Intervention; Learning Disabilities; Learning Strategies; Research Needs; State Surveys; Student Evaluation; Student Placement; Iowa; Collected Works, General; Information Analyses